2021
DOI: 10.1111/inr.12718
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Iranian nurses’ intention to leave or stay in the profession during the COVID‐19 pandemic

Abstract: Aim This study was conducted to explore the factors affecting nurses’ intentions to leave or stay in their profession during the coronavirus pandemic in Iran. Introduction Because the effectiveness of a healthcare response to a disaster depends on an available, skilled, and motivated healthcare workforce, it is essential to understand and address potential barriers to and reasons for the intentions of medical staff to leave or stay in their profession. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 37 publications
7
57
0
1
Order By: Relevance
“…The present study results also showed that turnover intention had a positive and significant correlation with job satisfaction. These results align with those of the study conducted by Varasteh et al ( 18 ). Job motivation, job satisfaction, and perceived organizational support are the predictors of nurses' tendency to leave their jobs ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study results also showed that turnover intention had a positive and significant correlation with job satisfaction. These results align with those of the study conducted by Varasteh et al ( 18 ). Job motivation, job satisfaction, and perceived organizational support are the predictors of nurses' tendency to leave their jobs ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…Turnover intention is one of the negative consequences of fatigue on HCWs. It is a common issue among nurses locally and internationally ( 18 ). In the last decade, the shortage of nurses has been a serious concern in most of the countries.…”
Section: Introductionmentioning
confidence: 99%
“… 47 It is also suggested that, despite fear of infection, one of the reasons for staying and accepting risks in a resilient or altruistic manner is a sense of commitment and awareness as a nursing professional. 48 In view of this, to mitigate the depression and fear of nurses, it is important to improve their working conditions, favoring the allocation of resources, and better living conditions during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Availability consists of such indicators as adequate numbers of nurses, physicians, and equipment (Batbaatar et al 2017). There is less than one nurse present for every hospital bed due to the COVID-19 pandemic, which has increased the nursing shortage to 0.7-0.8 (Varasteh et al 2021). Oppel et al (2017) reported that a lower rate of problems in terms of physician shortages was significantly associated with higher levels of patient satisfaction (Batbaatar et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%